MODEL KOLABORASI ETIS GURU DAN MASYARAKAT DALAM PENGUATAN KARAKTER DIGITAL PESERTA DIDIK DI ERA SMART EDUCATION - Azahra, Izza Aulia; Fatimah, Siti; Hasan, Talitha; Muhlisin, Muhlisin; Safitri, Hani Hasnah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The acceleration of digital transformation in education has heightened the urgency for an ethical collaboration model between teachers and communities to strengthen students’ digital character and ensure responsible engagement within increasingly complex Smart Education environments. This study aims to develop a conceptual model of ethical collaboration between teachers and communities in reinforcing students’ digital character in the Smart Education era. Using a library research approach, the study analyzes recent literature on digital ethics, digital pedagogy, character education, and the social role of communities within the educational ecosystem. The findings indicate that the formation of digital morality requires a triadic interaction among teachers, families, and communities, grounded in five ethical pillars: trust, transparency, participation, digital literacy, and accountability. The resulting model illustrates a hierarchical workflow beginning with the mapping of students’ digital conditions (input), the collaborative synergy between teachers and communities through ethical pillars (process), the establishment of an integrated digital character (output), and the creation of an ethical and sustainable Smart Education ecosystem (outcome). This research contributes to the development of an integrative, humanistic, and contextually relevant conceptual framework that aligns with the needs of Indonesia’s digital education landscape. The model may serve as a foundation for future research and for formulating more comprehensive digital character education policies. ABSTRAK Percepatan transformasi digital dalam pendidikan meningkatkan urgensi model kolaborasi etis antara guru dan masyarakat untuk memperkuat karakter digital peserta didik serta memastikan keterlibatan yang bertanggung jawab dalam lingkungan Smart Education yang semakin kompleks. Penelitian ini bertujuan mengembangkan model konseptual kolaborasi etis antara guru dan masyarakat dalam penguatan karakter digital peserta didik di era Smart Education. Menggunakan pendekatan library research, penelitian ini menganalisis literatur terkini mengenai etika digital, pedagogi digital, pendidikan karakter, dan peran sosial masyarakat dalam ekosistem pendidikan. Temuan menunjukkan bahwa pembentukan moralitas digital memerlukan interaksi tiga arah antara guru, keluarga, dan komunitas yang didasarkan pada lima pilar etika: trust, transparency, participation, digital literacy, dan accountability. Model yang dihasilkan menggambarkan alur kerja hierarkis yang dimulai dari pemetaan kondisi digital peserta didik (input), sinergi kolaboratif guru–masyarakat melalui pilar etis (proses), terbentuknya karakter digital berintegritas (output), hingga terciptanya ekosistem Smart Education yang etis dan berkelanjutan (outcome). Penelitian ini berkontribusi pada pengembangan kerangka konseptual yang integratif, humanistik, dan kontekstual terhadap kebutuhan pendidikan digital Indonesia. Model ini dapat digunakan sebagai dasar bagi penelitian selanjutnya maupun perumusan kebijakan pendidikan karakter digital yang lebih komprehensif.